PENGARUH FAKTOR-FAKTOR STORE ENVIRONMENT DAN FAKTOR-FAKTOR PRODUCT BRAND TERHADAP IMPULSE BUYING BEHAVIOR DI HYPERMART CIPUTRA WORLD SURABAYA - HENDRA HARTANTO, HENDRA HARTANTO (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2012)
The purpose of this research is to know whether store planning and merchandising, and national brand, licensed brand, and private label give significant influence both partially and totally toward impulse buying behavior in Hypermart Ciputra World Surabaya. This research is dealing with the store environment as the important factor in retailing, which consists of store planning and merchandising, and the effects toward impulse buying behavior. This research is also dealing with product brand, which is also an important factor in retail business, which consists of national brand, licensed brand, and private label, and the effects toward impulse buying behavior. The analysis result shows that store planning and merchandising are totally giving significant influence toward impulse buying behavior. The analysis result also shows that national brand, licensed brand, and private label are totally giving significant influence toward impulse buying behavior. Meanwhile partially, merchandising and national brand give significant influence toward impulse buying behavior.